INFLUENCE OF PREOPERATIVE POSTURING ON SUBFOVEAL FLUID HEIGHT IN MACULA-OFF RETINAL DETACHMENTS - Johannigmann-Malek, Navid; Kaye, Stephen B; Badawood, Shadi; Maier, Mathias; Baumann, Carmen (Retina (Philadelphia, Pa.), 2023)
To evaluate the effect of preoperative posturing on subfoveal fluid height (SFFH) in macula-off retinal detachment. A prospective study including patients with macula-off retinal detachment with SFFH measurable on optical coherence tomography (OCT) and duration of loss of central vision (LCV) ≤ 7 days. Linear OCT volume scans were performed at baseline, after 1 minute, 1 hour, 4 hours, and on the next morning. For the first hour, all patients remained in an upright position. Patients were then either instructed to posture until the surgery according to the location of the primary retinal break (posturing group) or were not given any instructions (control group). Twenty-four patients were included in the posturing group and 11 patients in the control group. There was no significant change in SFFH between baseline, 1 minute, 1 hour, and 4 hours. The mean SFFH in the control group increased by 243 µ m from 624 (±268) µ m at baseline to 867 (±303) µ m the next morning ( P < 0.01) but decreased in the posturing group by 150 µ m from 728 (±416) to 578 (±445) µ m ( P = 0.03). There was a significant association of the SFFH the next morning with posturing ( P < 0.01) and SFFH at baseline ( P < 0.01), but not with location of primary break ( P = 0.20). The change in SFFH from baseline to the next morning was significantly associated with posturing and primary break location ( P < 0.01), but not with SFFH at baseline ( P = 0.21). Preoperative posturing is an effective measure to prevent progression of macular detachment in macula-off retinal detachment.